Acute Carpal Tunnel Syndrome: Is It Only Wrist Fractures? A Case Series Report and Literature Review - Panos Christodoulou; Donald Osarumwense; Antonios Papadopoulos (Journal of Orthopaedic Case Reports)
Introduction: Acute carpal tunnel syndrome (CTS) is a rare but serious condition requiring prompt diagnosis and intervention to prevent permanent neurological deficits. This case series presents our department’s experience in managing this condition, highlighting diagnostic challenges, treatment strategies, and patient outcomes. Materials & Methods: This retrospective study analyses medical records of patients diagnosed with acute carpal tunnel syndrome from 2021 to 2023 within our coverage area. Information was extracted from medical records, including diagnostic codes and clinical assessments for all cases of acute carpal tunnel syndrome, diagnosed during the period from 2021 to 2023. Data analysed, include age, sex, medical history, symptoms, mechanism of injury, clinical features, imaging, management, and follow-up. Six native Scottish patients, aged 43 to 65, developed acute carpal tunnel syndrome due to various causes, including flexor sheath infection, wrist soft tissue injury, distal radius fractures (with and without plate fixation), and scaphoid fracture. Discussion and Results: Our case series highlights the heterogeneous presentation and aetiology of acute carpal tunnel syndrome, with causes ranging from trauma to infection. Early recognition remained challenging due to overlapping symptoms with other wrist pathologies. Surgical decompression was the mainstay of treatment, performed with variable urgency depending on clinical progression. Despite intervention outcomes were mixed. Some patients experienced full recovery while others had lingering symptoms. Conclusion: These findings underscore the importance of high clinical suspicion and prompt surgical intervention to optimise outcomes.